Public Perception of Healthy Indonesian Card Services in Wonosari Hamlet, Klantingsari Village, Tarik District, Sidoarjo Regency - Syifa Mamta; Kukuh Sinduwiatmo (Universitas Muhammadiyah Sidoarjo, 2021)
Health is the right of anyone who is an Indonesian citizen. This has been regulated in Indonesian laws and regulations. Therefore, the government as the representative and implementer of state policies must be able to create a healthy and prosperous society. In this case, the government is aiming for a program called KIS. The Healthy Indonesia Card or commonly referred to as KIS is the identity card of the participants of the National Health Insurance which is managed by the Health Social Security Administering Body. In the service of the Healthy Indonesia Card program, the community has been served well and in accordance with established regulatory procedures. The purpose of this study was to determine the public's perception of the Healthy Indonesia Card service in Wonosari hamlet, Klantingsari village, Tarik sub-district, Sidoarjo district. The method used in this research is qualitative. The subjects in this study were the people of the Wonosari hamlet. Data collection techniques used in this study were observation, interviews, and documentation. The data analysis and data interpretation techniques used are in accordance with the Miles and Hubermen concept, namely data reduction, data presentation and data verification. The results obtained in this study are that the public perception of KIS services in Wonosari hamlet, Klantingsari village shows a good perception. The community is very enthusiastic and feels very helped by the Healthy Indonesia Card program.